(untitled) (Journal of Hama University, 2024)
A good apical sealing is the key of the successful endodontic treatment. Therefore , the purpose of this study was to evaluate the efficiency of the ERRM sealing ability in Apicoectomy when it’s done in different angles (Oblique Cutting and Perpendicular Cutting Planes) and the next healing , In vitro study: 20 extracted human teeth with straight roots were instrumented and obturated,the samples divided into 2 groups based on the cutting angle of the apex, 3 mm of the root apex resected and retrograde preparations of 3mm were made using ultrasonic retro tips The cavities filled with ERRM ,cross sections were made and examined under the light Microscope, In vevo study 20 anterior single rooted teeth were referred to perform Apicoectomy, divided into 2 groups based on the cutting angle of the apex, ERRM was used to retro fill the apex , and the samples followed up to 12 months The results In vivo study showed at the confidence level of 95%, there are no statistically significant differences in the frequencies of the degree of healing variable between the two groups, The results In vitro study showed at the confidence level of 95%, there are no statistically significant differences in the frequencies of the variable degree of dye permeability between the two research groups So, paying attention to the procedural steps when performing the Apicoectomy leads to good outcomes for the surgical treatment Whether the comparisons were made, cutting apex at an angle perpendicular to the longitudinal axis of the root would lead to healing and treatment success With an emphasis on the importance of securing a good workspace that facilitates the practitioner to conduct debridement of the entire bony cavity